Assessing effect of idling on compression ignition engine operated with palm, jatropha and calophyllum biodiesel blends - Ashrafur Rahman, S.M.; Masjuki, Haji Hassan; Kalam, M.A.; Varman, Mahendra; Sanjid, A.; Abedin, M.J. (Institute of Industrial Applications Engineers, 2014)
Future lack of petroleum resources, price hike and environmental concerns have led to search for more environment friendly and renewable fuels. As an alternative fuel, biodiesel is considered as the most suitable alternative due to its environment friendly aspect and similar operation properties as diesel. In this study, Palm, Jatropha and Calophyllum biodiesel blends has been used to evaluate performance of a compression ignition engine operated at idling condition. Three idling modes were selected in which operating condition of engine were: a) 1000RPM 10% Load, b) 1200RPM 12% Load and c) 1500RPM and 15% Load. At high idling conditions biodiesel-diesel blends emit less HC and CO, but high amount of NOx compared to diesel fuel. At high idling conditions fuel consumption of biodiesel-diesel blends deteriorate. CIB20 emitted lowest HC and CO, and highest NOx at all idling modes